Comparison of LDH-Organic/Inorganic Compound Modified Materials as Adsorbents for Heavy Metal Adsorption: Characteristic Structure and Adsorption Mechanism - Normah, Normah; Lesbani, Aldes (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2024)
This study modified layered double hydroxide (LDH) with organic compounds in hydrochar made from rambutan peels (prepared by hydrothermal method) and polyoxometalate compounds (tipe Keggin K4[ -SiW12O40].nH2O compound and prepared by sol-gel method). The synthesis of modified material was conducted through the coprecipitation method. The material was then applied as an adsorbent for Fe²⁺ ions. The material's properties were analyzed using XRD (X-ray diffraction), FT-IR (Fourier-transform infrared spectroscopy), and BET surface area analysis. The physicochemical characteristics of the modified material, a combination of the pure LDH and hydrochar/polyoxometalate compounds, will influence the adsorption results of Fe²⁺ metal ions. Furthermore, its application as an adsorbent was analyzed through kinetic and isotherm parameters, which were found to follow the pseudo-first-order (PFO) and Freundlich models. The adsorption capacities for NiAl-LDH, NiAl-LDH/Hc (modified with Hc), and NiAl-LDH/POM (modified with POM) materials were 32.789 mg/g, 47.393 mg/g, and 90.091 mg/g, respectively. It can be concluded that the adsorption process occurs via physisorption, forming multilayer adsorbates at the adsorbents active sites. Copyright © 2024 by Authors, Published by BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)